THE BAJAKAH (SPATHOLOBUS LITTORALIS HASSK.) STEM PLANT EXTRACT EFFECT ON THE BLOOD GLUCOSE OF STREPTOZOTOCIN-INDUCED WISTAR MALE RATS - Wirjatmadi, Bambang; Isaura, Emyr Reisha (The Indonesian Journal of Public Health, 2024)
Introduction: Health practitioners have tried to reduce the prevalence of diabetes mellitus, which increases globally every year, but the result has not been optimal yet. Meanwhile, the indigenous people of the Dayak tribe from Borneo Island of Indonesia believe that the Bajakah plant (Spatolobus littoralis Hassk) can treat many diseases, including reducing blood glucose. However, the effect of the Bajakah stem plant extract on blood glucose regulation is still vague. Aims: Therefore, our animal-experimental research aimed to test the effect of the Bajakah stem plant extract using streptozotocin-induced Wistar male rats. Methods: We grouped the rats into K1, K2 (negative and positive control groups, respectively), P1, P2, and P3 (with additional Bajakah stem extract 50, 100, and 150 mg/kg body weight, respectively), with each group consisted of five rats. We collected blood glucose and insulin level at baseline (T1) and end of the intervention (T2). Results: This study found the highest mean ± standard deviation of insulin level was in the C2 group (5.10±0.84 µU/mL) and the lowest value in the X3 group (3.65±0.41 µU/mL). However, we found a significant difference in the blood glucose level at baseline and the end of the intervention (p<0.001). The highest reduction means value on blood glucose level was in the X3 group (T1: 471.40±89.24 mg/dL; T2: 122.80±12.50 mg/dL). Conclusion: The Bajakah stem plant's extract intervention affects the blood glucose level of Wistar male rats, possibly through the free radical's protection effect on the target cell receptor that binds to insulin and glucose.